A study of oxidative stress, thiol proteins and role of vitamin E supplementation in chronic obstructive pulmonary disease (COPD) - Anita M. Raut; Adinath N. Suryakar; Dilip Mhaisekar (Al Ameen Medical College, 2013)
Background: Lipid peroxide plays an important role in inflammatory lung disease. Increased epithelial permeability produced by cigarette smoke is likely to be mediated through depletion of thiol proteins. Imbalance between oxidants and thiol proteins is also an established fact in these patients. Materials & methods: In the present study 30 healthy non-smokers were served as controls and 20 patients with stable COPD were included. Their base line clinical examination, Malondialdehyde (MDA) as an oxidant, alpha tocopherol and erythrocyte superoxide dismutase (SOD) as an antioxidants and thiol proteins levels were measured. All above parameters were repeated after 12 weeks of supplementation with 400 IU of vitamin E daily. Results: We observed that the mean malondialdehyde levels in these patients at base line were high (p<0.001) than Control Plasma alpha-tocopherol, SOD and thiol proteins levels were low (p<0.001) in the patients compared to controls. Exogenous vitamin E (400 IU twice daily) Supplementation did not bring about any significant change in plasma Erythrocyte Superoxide Dismutase and vitamin E. But slight increase in the plasma thiol proteins levels was seen. The present study shows that initially the plasma lipid peroxide (MDA) levels were high antioxidant (alpha- tocopherol, SOD) and thiol proteins were low in patients with COPD. Exogenous supplementation with vitamin E increases slightly thiol proteins levels and brings down the levels of MDA showing attenuation of further damage. Conclusion: Our study confirmed the existence of oxidative stress and and the augmentation of antioxidant defenses as shown by slight increase in thiol proteins level. The antioxidant therapy is adjunct in lung disease patients and opens a promising field in prevention of oxidative stress related complications in these patients.